Implementation of Simple Additive Weighting (SAW) Method for Selecting Securities Company - Endang Lestari Ruskan; Nesya Leidy Azzura (STMIK Budi Darma, 2021)
A securities company has a purpose as an intermediary for stock trading between investors and the stock company to be purchased. Securities companies must be listed on the Indonesia Stock Exchange and supervised by the Financial Services Authority. The limited information that potential investors can receive regarding the criteria for selecting securities companies causes potential investors to have difficulty comparing each company. And no system supports decisions in this election. Based on the research, obtained eight assessment criteria in the selection of securities companies, as well as determining the weight of each criterion by calculating the Likert scale and determining the cost or benefit attribute for each criterion, as follows: initial deposit fee (15%) cost, transaction fee (12%) cost, stock recommendation fee (12%) cost, registration process time (12%) cost, support application rating (12%) benefit, company establishment (9%) benefit, customer service response (15%) cost, and features (15%) ) benefits. In this study, the authors use five alternatives. The calculation process results in a ranking, and the top-ranking is a highly recommended alternative based on existing criteria and weights. Then a website-based decision support system is made with the SAW method, which can assist in selecting securities companies based on the desired criteria and weights. Users can also view information on the value of each criterion given by each securities company